Determination of Ambient Dose Equivalent Using a Microprocessor-Controlled Universal Reference-Class Dosemeter (Journal of Science and Technology, 2025)
Ambient dose equivalent is determined at nine source-to-detector distances in a Secondary Standard Dosimetry Laboratory in a Cs-137 beam using a Physikalisch-Technische-Werkstaetten (PTW) ionisation chamber and Unidos electrometer as a measuring assembly. This work aims to estimate the gamma ambient dose equivalent resulting from air kerma rate distributions and subject the data generated to counting statistics to determine whether these data reflect proper instrument operation. The method of varying the source-to-detector distances was used. From the results, the total kinetic energy of all charged particles liberated by uncharged incident radiation per unit mass of material of the ionisation chamber ranged from 0.3168 ± 0.0146 μGy/s at an SSD of 1.0 m to 0.0151 ± 0.0007 μGy/s at 5.0 m within two standard deviations. The coefficient of variation among the various datasets ranged from 0.05% to 0.31%. Counting statistics of the generated data reflects proper measuring system operation and reliability. It is proposed that, in between calibrations, dosimetrists should consider relying upon counting statistics to check the output of their ionisation chambers for conformance to statistical laws.